Implementasi Peraturan Daerah (Perda) Kabupaten Lombok Timur Nomor 2 Tahun 2021 Tentang Pembatasan Timbulan Sampaah Plastik (Studi Kasus Di Kecamatan Masbagik) : Implementation Of East Lombok Regency Regional Regulation (Perda) Number 2 Of 2021 Concerning Restrictions On The Generation Of Plastic Waste (Case Study In Masbagik Sub-District) - andi fernanda; Masyhur (JURIDICA : Jurnal Fakultas Hukum Universitas Gunung Rinjani, 2023)
This research aims to find out how the implementation of East Lombok Regency Regional Regulation (Perda) Number 2 of 2021 concerning Restrictions on the Generation of Plastic Waste, in this case the focus of the research is in Masbagik Sub-district, because Masbagik sub-district is one of the areas that contributes the most waste due to There are two big markets, namely Masbagik Baru Market and Pasar Baru Paok Panggang.The research used in this research is empirical normative legal research, namely research from actions on the implementation of normative law. This type of research is field research, namely research carried out systematically and methodologically to reveal the data needed in research that comes from the field. And carry out a review of statutory provisions and look at the facts or realities that occur in the field.Based on the results of the research used, namely empirical normative research, it is clear that hierarchical regional regulations are made in accordance with statutory provisions and in their regulation, these regional regulations regulate various aspects regarding limiting the generation of plastic waste. From field data, the government has carried out socialization in accordance with its provisions, but implementing these regional regulations is difficult to implement due to several inhibiting factors, including legal factors, human resource factors, lack of public awareness, and lack of budget.